2023
DOI: 10.1021/acs.est.2c03964
|View full text |Cite
|
Sign up to set email alerts
|

Public Concern about Water Safety, Weather, and Climate: Insights from the World Risk Poll

Abstract: Water safety refers to the quality of one's drinking water and whether it lacks dangerous contaminants. Limited access to safe water is projected to impact approximately 5 billion people worldwide by 2050. Climate change and worsening severe weather events pose increasing threats to global water safety. However, people may not perceive links between climate change and water safety, potentially undermining their willingness to implement behaviors that improve water safety. Existing studies on water safety risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…This aligns with typical design activities, which are based on historical considerations. 1 Research has found that severe weather concerns are more predictive of water safety concerns than climate change concerns 65 and that adaptation efforts of wastewater utilities are motivated by improving resilience to past extreme events, not by addressing future climate change. 66 Use of historical events by participants to describe future risk could suggest a disconnect between risk awareness of current climate hazards and how future changes will affect those hazards.…”
Section: Resultsmentioning
confidence: 99%
“…This aligns with typical design activities, which are based on historical considerations. 1 Research has found that severe weather concerns are more predictive of water safety concerns than climate change concerns 65 and that adaptation efforts of wastewater utilities are motivated by improving resilience to past extreme events, not by addressing future climate change. 66 Use of historical events by participants to describe future risk could suggest a disconnect between risk awareness of current climate hazards and how future changes will affect those hazards.…”
Section: Resultsmentioning
confidence: 99%
“…Yet, because most populations in urban areas cannot afford the expense of a treated water system and lack access to infrastructure, their sense of quality relies on modest water systems or various sources to supply their drinking water demands [29]. In addition, perceptions of worsening water quality have been observed all across the world, in both rich and developing nations, and 'Thousands have survived without love, not one without decent water quality [30]. It should be emphasized that the types, magnitudes, and extents of water quality concerns vary from country to country, and even from region to region within a country.…”
Section: Community Member's Perceptions Of the Quality And Safety Of ...mentioning
confidence: 99%